Bibliometric analysis of recent research on 5-Fluorouracil (2015–2020) - Howard Ramirez-Malule, Wilson Cardona-G (Journal of Applied Pharmaceutical Science, 2021)
Cancer is one of the most widespread diseases in the world and causes millions of deaths every year. Currently, there are several anticancer treatments to deal with the different types of cancer reported around the world. However, most of them have both side effects and low selectivity to malignant cells. 5-Fluorouracil (5-FU) is used as firstline treatment against several types of cancer. Recently, hybrid and derivative molecules based on 5-FU have been reported as anticancer with high/modest activity, leading to a new and emerging therapy to treat cancer. The aim of this study was to carry out a bibliometric analysis of studies related to 5-FU in the field of chemistry. Data collection was carried out using the Scopus database, and VOSviewer 1.6.13 was used for data analysis and visualization. “5-Fluorouracil” was the term used in the search during a time span of 2015–2020. A total of 1,025 documents related to 5-FU were indexed in Scopus between 2015 and 2020, both included. Articles and reviews related to 5-FU have increased during the period of 2015–2020, starting and ending with 137 and 241 studies, respectively. The main areas, excluding chemistry, were (i) Biochemistry, Genetics, and Molecular Biology; (ii) Chemical Engineering; and (iii) Materials Science. Within these areas, the studies were focused on drug delivery, synthesis of anticancer compounds and their activity, molecular simulation, treatment of cancer cells, and drug resistance. Finally, the most productive countries on studies related to 5-FU, which also had the most robust collaboration network, were China, India, and the United States.
Keywords: 5-Fluorouracil, anticancer activity, bibliometric analysis